Role of high-dose interleukin-2 for melanoma in the age of cellular therapy - Mario Sznol; Elizabeth Buchbinder; Rodabe Amaria; Amod Sarnaik; David F McDermott; Michael B Atkins; Ann W Silk; Kim A Margolin; Michael T Lotze; Zeynep Eroglu; Virginia Seery; Allison Betof Warner; et al. (Journal for ImmunoTherapy of Cancer)
Interleukin-2 (IL-2) was one of the first immunotherapies in the treatment of patients with cancer. High-dose bolus IL-2 (HD IL-2) can induce durable complete or partial tumor regression in a small proportion of advanced melanoma and renal cell carcinoma patients. However, its potential for life-threatening side effects and requirement for inpatient administration limits its use to patients with excellent organ function treated at experienced centers. In 2024, following decades of foundational work at the National Cancer Institute, lifileucel became the first FDA-approved tumor-infiltrating lymphocyte (TIL) therapy for cancer. HD IL-2 is routinely given after TIL infusion to promote the survival and proliferation of the T cell product. In this context, fewer doses are given, and the parameters for holding an IL-2 dose are more conservative, as compared with HD IL-2 monotherapy, which has now fallen out of routine use. The lower number of doses, and possibly the effects of the preparative lymphodepletion, result in much less cytokine-related toxicity. Nevertheless, concerns related to HD IL-2 toxicity persist and possibly impact decisions to offer TIL when indicated. Here, we discuss the differences in the administration of HD IL-2 as a monotherapy vs an adjunctive therapy following TIL infusion, in an effort to demystify the toxicity of HD IL-2 in the era of cellular therapy.